2019
DOI: 10.1038/s41598-019-40479-9
|View full text |Cite
|
Sign up to set email alerts
|

Egg-laying decisions based on olfactory cues enhance offspring fitness in Stomoxys calcitrans L. (Diptera: Muscidae)

Abstract: Selection of oviposition substrate is critical in holometabolous insects. Female stable flies, Stomoxys calcitrans , locate and select vertebrate herbivore dung in which they lay their eggs. However, the preference for vertebrate herbivore dung by S . calcitrans females, its fitness consequences for offspring, and the semiochemicals used to locate and select oviposition substrates remain unclear. Using oviposition choice tests and life table … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 63 publications
4
45
0
2
Order By: Relevance
“…Consequently, our study found no evidence in support of the HHSP. Our results imply that preference for particular dung types by female S. calcitrans for oviposition (Baleba et al, 2019) is an innate rather than learned behaviour. Rojas and Wyatt (1999) demonstrated that experience of the cabbage moth caterpillar Mamestra brassicae (Lepidoptera: Noctuidae) did not affect oviposition behaviour of their females.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…Consequently, our study found no evidence in support of the HHSP. Our results imply that preference for particular dung types by female S. calcitrans for oviposition (Baleba et al, 2019) is an innate rather than learned behaviour. Rojas and Wyatt (1999) demonstrated that experience of the cabbage moth caterpillar Mamestra brassicae (Lepidoptera: Noctuidae) did not affect oviposition behaviour of their females.…”
Section: Discussionmentioning
confidence: 65%
“…During all the bioassays, we used camel and sheep dung as rearing substrate based on the difference in their physicochemical properties (Baleba et al, 2019) The amount of substrate in each test arena was 50 g. At 10 min after setting up each replicate, larvae found on a substrate were considered to have made a choice.…”
Section: Experience Testmentioning
confidence: 99%
See 3 more Smart Citations